-9-4+2M=-9-7M+5

Simple and best practice solution for -9-4+2M=-9-7M+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9-4+2M=-9-7M+5 equation:


Simplifying
-9 + -4 + 2M = -9 + -7M + 5

Combine like terms: -9 + -4 = -13
-13 + 2M = -9 + -7M + 5

Reorder the terms:
-13 + 2M = -9 + 5 + -7M

Combine like terms: -9 + 5 = -4
-13 + 2M = -4 + -7M

Solving
-13 + 2M = -4 + -7M

Solving for variable 'M'.

Move all terms containing M to the left, all other terms to the right.

Add '7M' to each side of the equation.
-13 + 2M + 7M = -4 + -7M + 7M

Combine like terms: 2M + 7M = 9M
-13 + 9M = -4 + -7M + 7M

Combine like terms: -7M + 7M = 0
-13 + 9M = -4 + 0
-13 + 9M = -4

Add '13' to each side of the equation.
-13 + 13 + 9M = -4 + 13

Combine like terms: -13 + 13 = 0
0 + 9M = -4 + 13
9M = -4 + 13

Combine like terms: -4 + 13 = 9
9M = 9

Divide each side by '9'.
M = 1

Simplifying
M = 1

See similar equations:

| 24x^2+14x+108=0 | | 3*x^2=8-2x | | h(x)=x^4-4x+2 | | 4(3n-2)=(7n+4)+6 | | 45+3x+r=180 | | -.014x^2+.68x=0 | | 3x+23=52 | | 2(3x-1)+9=4x+15 | | A+bxc= | | 2x-3*2=x-9 | | 3x-124-12x=128 | | -4x+10=2y | | 2x-3+2x-3=x+9 | | 11x+19=41 | | 5x^6+x^4+5x^2+7x-65=0 | | -7k+3-6k=-35 | | 6x-4=7(x-8) | | y(2-y)=6-[y(y)+3y-4] | | 13=0.7x+2.50 | | x^2-120x=-2780 | | 3x+8y=-16 | | tanx=2.0417 | | 4(r+1.4)-6r=7.3 | | -5x-8y=59 | | 3a+b=5c | | 5x^2-7y^2=0 | | -4(-12+k)=-12 | | 2x^2+6x-6x-7+3=0 | | -16-3x=40-5x | | 5u(u+9)(u-6)=0 | | 6z-4z+2z= | | 6(u+2)=48 |

Equations solver categories